BANDWIDTH AND GAIN ENHANCEMENT OF MICROSTRIP ANTENNA USING DEFECTED GROUND STRUCTURE AND HORIZONTAL PATCH GAP - Dian Rusdiyanto; Catur Apriono; Dian Widi Astuti; Muslim Muslim (SINERGI, 2021)
This research proposed microstrip antenna design using the Defected Ground Structure (DGS) and horizontal patch gap (HPG) for bandwidth and enhancement purposes. This design is to reduce the weakness of a microstrip antenna, which has small gain and narrow bandwidth. The design was simulated in CST Microwave Studio with a working frequency of 2.4 GHz. The design consists of three stages model, i.e., conventional design, DGS modification, and the combination DGS using a Horizontal Patch Gap (DGSHPG). The radius of the conventional circular patch is 16.7 mm. The substrate has 4.6 of dielectric constant, 1.6 of substrate height, and 0.025 of the loss tangent. The simulation results show that the DGS design produces more bandwidth and gain than a conventional design, where the bandwidth and gain improvement are 421.2 MHz and 1.73 dB, respectively. The DGS model is combined with a gap that separates the circular patch (DGSHPG) to achieve the optimum design. The results show the bandwidth and gain improvement of more than 50% and 18.1% compared to the DGS design, respectively. Other parameter performance also shows improvement, such as a reflection factor with -53.3 dB at the center frequency. The physical change also influences the patch’s radius, where it is reduced around 1.4 mm or 8.4% from the original design. Overall, the proposed design has succeeded in achieving bandwidth and gain enhancement and reducing the patch dimension.